THE MAIN FACTORS THAT FORM SOCIAL ACTIVITY IN YOUNG PEOPLE: EDUCATION, CULTURE AND MEDIA (American Journal of Business Management, Economics and Banking, 2025)
This academic article analyzes the formation of youth social activity through key factors such as education, culture, and media. Education, culture, and media play a significant role in developing the youth’s consciousness, encouraging their active participation in societal changes. The paper emphasizes the role of the education system in preparing youth for social responsibility, the influence of culture in shaping moral values, and the importance of media in increasing youth engagement. These factors, working in harmony, serve to involve youth in societal transformations.